Gestational HTLV: prevention and nursing care in Primary Care (Research, Society and Development, 2021)
The present study aims to explain about gestational HTLV: prevention and nursing care in primary attention and to point out in full what the main manifestations suffered by patients with diagnosis of the disease are. This is a narrative bibliographic study whose methodological trajectory is based on the readings, exploratory and selective exploration of bibliographic research material, searching for databases: the bibliographic survey was carried out in the following electronic media: Scielo, LILACS, Medline, BDENF, in the months of April to November of 2021, publications containing relevant information on the subject in question. Words were used as descriptors for international databases: HTLV-I infections and Infectious Pregnancy Complications, HTLV-I infections and nursing care, HTLV-I and gestation infections. The inclusion criterion for materials for use was articles, books, magazines and websites that addressed the topic. It is concluded that nursing care provided to HIV-positive pregnants and to HTLV-I should be guided in the direction of non-breast-feeding, making it clear to the pregnant person the risk of transmission of the virus and the possibility of other pathological processes arising. It is therefore necessary to strengthen the importance of the preparation of the nursing team, in the reception and treatment of HIV-positive pregnant women, as well as to expand the findings on such problems through health education and guidance, so that the collective appropriates sufficient knowledge with a focus on promoting actions to prevent the virus and reducing possible staples.